Antifungal Activity of Clove (Syzygium aromaticum) Essential Oil against Aspergillus parasitus isolated from Okra (Abelmoschus esculentus) (International Journal of Food and Nutritional Sciences, 2022)
Aspergillus parasitus is a ubiquitous and opportunistic fungal pathogen that poses a significant threat to both human health and various agricultural products and has shown resistance to conventional antifungal agents. The increasing incidence of fungal infections and the emergence of drug-resistant strains have prompted the search for novel and effective antifungal agents. The present study aims to investigates the antifungal activity of clove essential oil against Aspergillus parasitus, aiming to explore its potential as an alternative or adjunct therapeutic agent. The antifungal activity of the essential oil was evaluated using Poisoned Food Technique. Aspergillus parasitus was isolated from okra seeds. The results demonstrated significant antifungal activity of different concentrations of clove essential oil viz., 20%, 40%, 60%, 80% and 100% at 1000 ppm against Aspergillus parasitus. The findings of this study demonstrate the promising antifungal activity of clove essential oil against Aspergillus parasitus. The presence of eugenol and β-caryophyllene may contribute significantly to the observed efficacy. Clove essential oil could serve as a natural and accessible therapeutic option for the treatment of Aspergillus parasitus infections.